Effect of conducting filament radius on local temperature and activation power of ON-state ReRAM device. (23rd August 2021) - Das, Om Prakash; Pandey, Shivendra Kumar
Abstract: The formation and disruption of conducting filament (CF) are responsible for the SET/RESET switching of resistive random access memory (ReRAM). The ReRAM enters into a low resistive state soon after the complete formation of CF and the process is followed by the radial growth of CF during the ON-state. The present investigation aims to develop a numerical and analytical model to realize the effect of CF radius on local temperature rise and activation power, combining the thermal reaction model (TRM) and power signature model. The numerical investigation is carried out using finite element method to obtain the local temperature rise and temperature distribution across the device. The numerical results show a similar increment pattern of local temperature as of analytical TRM i.e. the local temperature increases linearly with a rapid growth rate of ∼63% in initial CF radii and then gradually attains a steady-state temperature with ∼10% increment in higher CF radii. The relationship between resistance and compliance current is calculated which obeys the same reported trend in other switching oxides like TiO X, CuO, NiO. Additionally, the activation power is determined where the resistance decreases (101.87–0.25 KΩ) due to the CF radial growth, which results in four orders of exponential increment in activation power from ∼0.04 µ W to 500 ± 100 µ W. The power signature of numerical TRM is validated with that analytical TRM where the device attends a steady-state temperature after a certain CF radius (>25 nm) along with the activation power.